Differential Sensitivity of Maize Hybrids to Nicosulfuron - Bevilaqua, Natalia da Cunha [UNESP]; Costa, Renato Nunes [UNESP]; Giovanelli, Bruno Flaibam [UNESP]; Pereira, Vinicius Gabriel Caneppele [UNESP]; Krenchinski, Fábio Henrique [UNESP]; Carbonari, Caio Antonio [UNESP]; Velini, Edivaldo Domingues [UNESP] (MDPI, 2025)
Maize hybrids exhibit varying levels of tolerance to the herbicide nicosulfuron, influenced by the environment, plant developmental stage, and herbicide rate. The objective of this study was to determine the sensitivity of maize hybrids to nicosulfuron through biochemical markers. Eight hybrids were treated with 120 g ha−1 of nicosulfuron at the V2 and V6 growth stages in a greenhouse experiment. The plants were collected at one day after the application of the herbicide to determine the contents of nicosulfuron, aminobutyric and quinic acids and valine, leucine, and isoleucine amino acids. Plant height and phytotoxicity were evaluated at 7, 14, 21, and 28 DAA. The plants were collected at 28 DAA to determine the shoot dry weight. The results indicated that sensitivity to nicosulfuron varied among the eight hybrids studied, with the V2 stage exhibiting higher herbicide accumulation, greater height reduction, and increased phytotoxicity. Aminobutyric acid levels increased in all hybrids after herbicide application, with a stronger correlation between its accumulation and growth inhibition at the V2 stage. These findings suggest that V2 is the most suitable stage for distinguishing hybrid sensitivity to nicosulfuron.
Keywords: ALS inhibiting herbicides; amino acids; aminobutyric acid; sulfonylurea